Motivation and Attitudes toward English as a Foreign Language among Malang Secondary Students - Sinta, Shofi Ayu; Nurmukminatien; El Khoiri, Niamika (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
This study explores the motivation and attitudes of junior and senior high school students in Malang City towards learning English as a foreign language. It explains the needs of understanding about students’ motivation and attitude in Malang. Using a descriptive quantitative design, data were collected from 262 students across multiple schools through a structured questionnaire adapted from Kirkpatrick et al. (2024). The results reveals that most students have positive attitudes toward English, showing the interest (64,1%), the understand (68,9%), the importance (62,6%), and students’ engagement in learning English. Most of students reckon speaking was the most exciting activity (32,1%), while grammar was the most difficult (35,5%). These findings support existing motivational theories that can measure students’ motivation in learning English. Further researchers are suggested to consider comparing different levels of education, types of schools, or regional backgrounds to explore how socio-cultural.